Cognitive Dissonance, Business Longevity, and Spiritual Values of Business in Bali Post-Pandemic - Ni Made Cantika Putri Aristya Sandy; Auditia Setiobudi; Teofilus Teofilus (University of Merdeka Malang, 2022)
This study refers to a phenomenon among Balinese business practices that is faced with new situations so that a conflict arises between beliefs and something that must be lived but is considered contrary to attitudes. The new situation is the impact of the pandemic that can affect business continuity. The purpose of this study was to examine the effect of Cognitive Dissonance on Business Longevity and the effect of Cognitive Dissonance on Business Longevity moderated by Spiritual Values. The research method used is quantitative method and purposive sampling as sampling. The data obtained were then processed with SPSS. This study has a sample of 120 respondents who are business practices in Badung, Bali. The results showed that Cognitive Dissonance had a significant effect on Business Longevity. Moreover, there is no moderating effect exerted by Spiritual Value in the relationship between Cognitive Dissonance and Business Longevity. However, this study found that Spiritual Values can have a partial effect on Business Longevity.